2008
DOI: 10.1007/s11251-008-9065-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between students’ conceptions of constructivist learning and their regulation and processing strategies

Abstract: The present study investigated relationships between students' conceptions of constructivist learning on the one hand, and their regulation and processing strategies on the other hand. Students in a constructivist, problem-based learning curriculum were questioned about their conceptions of knowledge construction and self-regulated learning, as well as their beliefs regarding their own (in)ability to learn and motivation to learn. Two hypothesized models were tested within 98 psychology students, using a struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 37 publications
4
40
2
5
Order By: Relevance
“…Overall, they confirm the strong interrelations between students' processing and regulations strategies, learning conceptions, and learning motivations that form the core of the learning patterns model (Edelbring 2012). For example, in a problem-based curriculum, Loyens et al (2008) found structural positive relations between Dutch students' constructive conceptions of learning on the one hand and their use of deep processing and self-regulation strategies on the other hand. The learning conceptions 'construction of knowledge' was negatively related to external regulation and lack of regulation.…”
Section: Internal Relationships and The Dimensionality Of Learning Pasupporting
confidence: 60%
See 1 more Smart Citation
“…Overall, they confirm the strong interrelations between students' processing and regulations strategies, learning conceptions, and learning motivations that form the core of the learning patterns model (Edelbring 2012). For example, in a problem-based curriculum, Loyens et al (2008) found structural positive relations between Dutch students' constructive conceptions of learning on the one hand and their use of deep processing and self-regulation strategies on the other hand. The learning conceptions 'construction of knowledge' was negatively related to external regulation and lack of regulation.…”
Section: Internal Relationships and The Dimensionality Of Learning Pasupporting
confidence: 60%
“…Many studies reviewed in this paper have used Structural Equation Modelling (SEM) as an elegant way to deal with a large number of variables at the same time (e.g. De Clercq et al 2013;Loyens et al 2008;Martínez-Fernández and Vermunt 2015;Zhu et al 2008). Fryer et al (2016) used a longitudinal variant of SEM to analyse variables from two waves of data collection from the same students.…”
Section: Methodological Advances In Learning Patterns Researchmentioning
confidence: 99%
“…Learning strategies were measured via their cognitive aspects (Ito, 1996;Pintrich & De Groot, 1990), their meta-cognitive aspects (Ichihara & Arai, 2006), and self-motivational strategy scales (Ito & Shinto, 2003) that included 23 items (α = .87). These items have been used in previous studies (Jones, Estell, & Alexander, 2008;Loyens, Rikers, & Schmidt, 2008). Participants were asked to rate how often they use learning strategies using a 5-point scale ranging from 1 (Not apply) to 5 (Apply), and averages derived.…”
Section: Methodsmentioning
confidence: 99%
“…It comes from cumulative experiences and sharing of different ideas and then changing one's internalized response to those ideas or views (Bednar, Cunnigham, Duffy, Perry, 1995). A pilot with already some years of flying have a strong background in aviation that guided constructivism provided by the facilitator for the pilots need in transitioning can have a positive effect in their learning and adaption to the new avionics platforms (Loyens et al 2008). This, however, cannot be self-regulated instruction but guided positive reinforcement coupled with a scaffolding methodology (Loyens et al 2008;Brown, 1987).…”
Section: Analyzing the Evidencementioning
confidence: 99%
“…A pilot with already some years of flying have a strong background in aviation that guided constructivism provided by the facilitator for the pilots need in transitioning can have a positive effect in their learning and adaption to the new avionics platforms (Loyens et al 2008). This, however, cannot be self-regulated instruction but guided positive reinforcement coupled with a scaffolding methodology (Loyens et al 2008;Brown, 1987). Homko (2011) in his research article stated What can be taken from this observation is an understanding that older people could well be taught to use technology in much the same way as younger people are taught.…”
Section: Analyzing the Evidencementioning
confidence: 99%